2016
DOI: 10.1175/jpo-d-16-0042.1
|View full text |Cite
|
Sign up to set email alerts
|

Downfront Winds over Buoyant Coastal Plumes

Abstract: Downfront, or downwelling favorable, winds are commonly found over buoyant coastal plumes. It is known that these winds can result in mixing of the plume with the ambient water and that the winds influence the transport, spatial extent, and stability of the plumes. In the present study, the interaction of the Ekman velocity in the surface layer and baroclinic instability supported by the strong horizontal density gradient of the plume is explored with the objective of understanding the potential vorticity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…The interaction between surface intensified river plumes and downwelling favorable winds induces geostrophic sheared flows (weak to moderate winds) in regions of strong horizontal density gradients (Spall and Thomas, 2016). In their study, high wind conditions induced circulation that prevails over the density current (Spall and Thomas, 2016). In our study, intense winds induce ageostrophic sheared currents that dominate over the density current which is similar to their key findings.…”
Section: River Plume Dynamicssupporting
confidence: 88%
See 3 more Smart Citations
“…The interaction between surface intensified river plumes and downwelling favorable winds induces geostrophic sheared flows (weak to moderate winds) in regions of strong horizontal density gradients (Spall and Thomas, 2016). In their study, high wind conditions induced circulation that prevails over the density current (Spall and Thomas, 2016). In our study, intense winds induce ageostrophic sheared currents that dominate over the density current which is similar to their key findings.…”
Section: River Plume Dynamicssupporting
confidence: 88%
“…The destratification in summer is also linked to a high wind event inducing frontolysis and the growth of ageostrophic shear. Similar results have been observed in idealized simulations in stratified buoyant coastal plumes where the wind stress is linked to the reduction of PV and therefore to destratification (Spall and Thomas, 2016;Lv et al, 2020). In their study, the restratification processes are observed during wind relaxation periods when the geostrophic shear becomes dominant.…”
Section: River Plume Interior Mixingsupporting
confidence: 85%
See 2 more Smart Citations
“…1a). Since the horizontal scale of the frontal eddies is O(10 km) (e.g., Spall and Leif 2016), the 3-km resolution is considered eddy-permitting. In the vertical direction, 7 surface layers were arranged at depths of less than 34 m to represent the surface elevations due to surface gravity waves, whereas 77 levels deeper than 34 m…”
Section: Modelling Configurationmentioning
confidence: 99%